Transformasi Budaya Bapukung: Dari Kearifan Lokal Menuju Strategi Efektif dalam Pemberdayaan dan Manajemen Peran Ganda Ibu Rumah Tangga: Cultural Transformation of Bapukung: From Local Wisdom to Effective Strategies in Empowering and Managing the Dual Role of Mothers in the Household - Saufi, Muhammad; Rizqina, Sila; Cahya, Nila (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The community service partners are housewives in Cindai Alus Village, Banjar Regency, who, in addition to their domestic roles, are also actively managing home-based microenterprises, particularly in the production of traditional Banjar snacks. This condition presents challenges, as most of them still have toddlers who require full attention, often disrupting the continuity of production. The program was implemented to enhance the ability of homemakers to manage their time, balance family roles with productivity, and reintroduce the traditional bapukung method, which functions to soothe children, support better sleep, and promote child development. The approach included socialization, training, and hands-on practice in utilizing sasirangan fabric as a material for the bapukung cradle, while also providing economic value through the development of handicraft skills. The results of the program indicate an increased understanding of daily time management, improved skills in producing sasirangan fabric products, and greater awareness of the benefits of bapukung in reducing interruptions during production activities. By applying this method, homemakers can allocate their time more effectively, thereby improving business productivity. This program concludes that strengthening the capacity of homemakers through traditional and innovative approaches can encourage economic welfare while simultaneously preserving local wisdom.